Semeando no voluntariado para colher cidadania: um estudo sobre motivações para o trabalho voluntário, percepções e atitudes cidadãs - Amorim, Amanda Florense Alves (2018)
This research aimed to analyze the relationship between the motivations for volunteering and citizenship, focusing on volunteers in the health area in the State of Paraíba. In this sense, a theoretical framework was developed aiming at the general basis of citizenship, volunteering, motivation for volunteer work, as well as the intercession of these themes. And then, for the continuation of the analyzes were developed statistical techniques, such as: descriptive measures, tests of correlations, variances and differences of means between groups. For the data collection process, two questionnaires were used: one to categorize voluntary motivations, prepared and validated by Cavalcante (2016), and one adapted from the Citizen Audit e Ferraz (2017), a census created by the Social and Economic Research Council of England, to the analysis of attitudes and behaviors linked to citizenship. These questionnaires were submitted to two samples of 222 people: volunteers and non-volunteers, making it possible to make comparisons between both groups regarding citizen practice. In the analysis of the results, the descriptive measures of the instruments used were demonstrated, in which the means of motivation for learning, followed by altruistic, were highlighted as the most expressive among the volunteers. Comparative analyzes were also performed between volunteers and non-volunteers from the t-test, as well as tests of correlation between motivations for voluntary work and social, political and civil rights. Finally, it can be said that volunteers working in the health of the State of Paraíba in the quest for learning as a motivation for more expressive volunteerism, for altruistic motivation and search for social justice. From the obtained results it was still evidenced that as people who carry out volunteer work, in general, presented higher averages between as dimensions of citizenship in parties with which they do not act without volunteering, leading us to the conclusion that the voluntary action is related to positive way with the understanding and exercise of an active citizenship, although this one is under construction.